2006
DOI: 10.1038/sj.jid.5700009
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Class I Chain-Related Gene A Polymorphisms and Extended Haplotypes Are Associated with Familial Alopecia Areata

Abstract: Alopecia areata (AA) is characterized by hair loss in patches and may progress to total loss of scalp hair, or total loss of scalp and body hair. The major histocompatibility complex (HLA) is associated with susceptibility to AA, as well as other autoimmune diseases. In addition to HLA molecules, non-HLA molecules including the major histocompatibility complex class I chain-related gene A (MICA), a stress-inducible antigen, are also associated with several autoimmune diseases. To investigate associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 34 publications
4
30
0
Order By: Relevance
“…[24][25][26] Of interest, low vitamin D levels were recently found in 90.7% of patients with alopecia areata, which is another T-cell mediated autoimmune disease with HLA-DR and HLA-DQB1 associations the same as MF and SS. [27][28][29][30] It was unexpected to find a difference in correction rate based on the type of vitamin D oral supplement. Individuals treated with 1000 IU of oral vitamin D3 were less likely to achieve normal serum levels than those treated with 50,000 IU of vitamin D2 twice a week.…”
Section: Discussionmentioning
confidence: 89%
“…[24][25][26] Of interest, low vitamin D levels were recently found in 90.7% of patients with alopecia areata, which is another T-cell mediated autoimmune disease with HLA-DR and HLA-DQB1 associations the same as MF and SS. [27][28][29][30] It was unexpected to find a difference in correction rate based on the type of vitamin D oral supplement. Individuals treated with 1000 IU of oral vitamin D3 were less likely to achieve normal serum levels than those treated with 50,000 IU of vitamin D2 twice a week.…”
Section: Discussionmentioning
confidence: 89%
“…However, the altered HPA activity was likely a consequence of the immune response associated with AA. In this study, the increased incidence of AA in 8-month-old (Barahmani et al 2006), and it was identified as a potential candidate gene and part of an extended HLA haplotype that may contribute to susceptibility of AA in humans (Barahmani et al 2006). MICA is expressed on the surface of epithelial cells of the gastric and intestinal mucosa (Stephens 2001), endothelial cells, fibroblasts, monocytes (Zwirner et al 1999), and keratinocytes within the epidermis and hair follicles (Tay et al 2000).…”
Section: Discussionmentioning
confidence: 97%
“…NK, NKT, and some CD8 þ T cells) as well as NKG2D-activating ligands from the MICA (MHC I-related chain A) family may also have a key role in AA pathogenesis (Ito et al, 2008a, b;Petukhova et al, 2010). This is supported by genotyping (Barahmani et al, 2006) and genome-wide association study evidence (Petukhova et al, 2010;Jagielska et al, 2012). Interestingly, the injection of peripheral blood mononuclear cells from healthy individuals that were enriched for NKG2D þ or CD56 þ cells and activated by IL-2 into healthy human scalp skin transplanted onto severecombined immunodeficient mice can induce a hair loss pattern that copies the human AA phenotype (Gilhar et al, 2013).…”
mentioning
confidence: 92%